Black Lives, White Witnesses: An Argument for a Presentist Approach to Teaching Aphra Behn's Oroonoko - Sharon Smith (ABO : Interactive Journal for Women in the Arts 1640-1830, 2023)
This essay outlines a presentist approach to teaching Aphra Behn’s Oroonoko (1688), in which a white woman witnesses a Black man’s brutal execution at the hands of enslavers. This approach explores the capacity of Behn’s novel—a colonialist narrative scholars frequently identify as troubling or frustrating—to generate discussions about “white witnessing,” particularly white people’s consumption of images of Black people in peril. This includes recent videos of Black people killed by police or white citizen vigilantes. Many Black individuals identify these videos as traumatizing, frequently noting how they have failed to spur structural reform. Of central concern in the classroom discussion described in the essay is the sympathy white witnesses experience in response to images of racist violence, a feeling that can bring reassurance—even pleasure—to the white witness but that in and of itself does little, if anything, to address the systemic causes of such violence and may actually serve to sustain them. In addition to considering how instructors can draw upon this novel from the past to generate discussions about critical issues of the present, the essay describes how they might place Oroonoko in conversation with texts from diverse periods, places, and genres in order to expose the limitations of and fill the gaps in Behn’s narrative.